2019
DOI: 10.1016/j.acap.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Components of Resilience on Obesity Across Income Strata in the National Survey of Children's Health

Abstract: Resilience, specifically emotional resilience, may be a protective factor against obesity in children regardless of income stratum. Physical activity of the child is associated with greater emotional resilience, and better maternal health may mediate the association between this component of resilience and weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Given our high‐risk sample of youth exposed to long‐term adversity, proficient EF may be conceptualized as a measure of resilience, which is described as the capacity to adjust, adapt, self‐stabilize, and self‐regulate in the context of adversity (42). Findings from a nationally representative study of youth aged 10 to 17 years found that child resilience, measured using indicators of curiosity, completing tasks, and staying calm/controlled when challenged, was associated with a lower risk for obesity (43), and that the relation was strongest among youth living in high‐poverty households, which has tremendous implications for prevention. Our findings provide evidence that EF may confer a degree of obesity resilience for some youth exposed to poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Given our high‐risk sample of youth exposed to long‐term adversity, proficient EF may be conceptualized as a measure of resilience, which is described as the capacity to adjust, adapt, self‐stabilize, and self‐regulate in the context of adversity (42). Findings from a nationally representative study of youth aged 10 to 17 years found that child resilience, measured using indicators of curiosity, completing tasks, and staying calm/controlled when challenged, was associated with a lower risk for obesity (43), and that the relation was strongest among youth living in high‐poverty households, which has tremendous implications for prevention. Our findings provide evidence that EF may confer a degree of obesity resilience for some youth exposed to poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that emotional resilience in adolescents is preventative against obesity. 22 Therefore, the approaches aiming to enhance emotional resilience may contribute to combating obesity. Regular physical activity, which is recommended in obesity treatment, provides positive outcomes in several obesity-related diseases such as cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals are more exposed to stressful life events and thus show higher emotional stress levels. Moreover, it has been reported that emotional resilience in adolescents is preventative against obesity 22 . Therefore, the approaches aiming to enhance emotional resilience may contribute to combating obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological resilience could serve as a protective factor that reduces the likelihood of obesity [ 26 ], particularly for those with low SS. Such protective effects could be due to the role of resilience in decreasing stress levels and resultant eating behaviors [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimism—a personality characteristic consistently reported in resilient and thriving individuals—has been associated with higher intake of fruit, vegetables, grains and lower intake of sugar [ 30 , 31 ]. Together, these findings suggest psychological resilience may play a role in reducing unhealthy eating behaviors and risk for obesity [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%